Application of Dic Based on Inverse Compositional Algorithm in Fish Skin Tensile Test - Ge, Pengxiang; Ma, Wanlong; Zhang, Mei; Li, Guihua (2018 11th International Conference on Intelligent Computation Technology and Automation (ICICTA), 2018)
Digital image correlation method (DIC) has higher requirements in displacement measurement. For this reason, the application of inverse compositional algorithm in sub pixel displacement measurement is studied, and compared with the traditional algorithms. The grass carp skin high precision stretch test was taken as the research object, and the inverse compositional algorithm was tested experimentally in the whole pixel and sub pixel level displacement measurement. The results show that the inverse compositional algorithm has obvious advantages in measurement accuracy and meets the requirements of DIC for measurement accuracy in displacement measurement. It provides a good theoretical and experimental basis for full field strain measurement.